The social imaginary, Jacques Lacan, and the African Christian diaspora in Europe - Eriksen, Kare (Department of Religious Studies, 2023)
This thesis is a theoretical discussion that brings together three major fields of enquiry. It is structured in two sections. In Part One, the notion of the social imaginary, as a theoretical response to the challenges of 'multiple modernities', is compared to the theories of the psychoanalyst Jacques Lacan. In Part Two, the findings from this comparison are applied to reflect on contemporary issues in Christianity in and out of Africa. The notion of the social imaginary represents a way of addressing issues of society through the lens of the subject's imagination, instead of thinking of society as external and bounded. Lacan helps us to ground this approach in a psychological appraisal of the subject, whereby the subject is 'lacking' and the external world functions as a source of identification and cognition that serves to cover up this void. This perspective allows us to re-think 'imagination' in terms of signification as, for Lacan, the writing of the self hinges on the subject's appropriation of signifiers. Similarly, the social imaginary could be understood in terms of the subject's assembly of images. The twist, for Lacan, is that the meaning ( signified) of the signifier can never be finally determined, which raises fundamental questions about the production of knowledge and the coherence of the social-ideological reality. This traumatic gap in the signifying chain is what Lacan's enigmatic order of the Real is about, and its repression requires from the subject a response that oscillates between thought and affect. Following Slavoj Zizek, we can develop a Lacanian parallel to the social imaginary around the notion of the master-signifier that 'quilts' the production of meaning and anchors our social reality. Crucially, it does so by producing 'objects' that address the subject's desire on the level of cognition as well as enjoyment, of thought and affect. The notion of the master-signifier provides an appealing approach to examine the Charismatic Christian revival taking place in Africa. Taking Ghana as example, I argue that this 'prosperity' -themed awakening could be understood as a response to a context in which symbolic and material voids converge to create a deficit of meaning in the postcolony. The effects of these developments also spill into Africa's 'new' diaspora in Europe, where African-led churches represent an intriguing test-case for a Lacanian reading of 'multiple modernities'. A central point emerging from this analysis is that the diaspora context requires quilting operations that halt not only the sliding of the signified, but of the signifier as such. This analysis could also be read as an indirect contribution to the debate on the significance of the African Christian diaspora in Europe, especially in the light of the idea of 'reverse mission'. In this regard, this thesis urges one to note the changing outlooks of African Christianity from the African continent to Europe, reflecting the changing and expanding psychological needs of its adherents.